Perceived Brand Value And Consumer Involvement On Brand Loyalty - Ismanto Ismanto; Muhamad Stiadi; Ulfasari Sukardi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study aims to find out: (1) The Effect of Perceived Brand Value on Brand Loyalty in Suzuki Brand Motorcycle Users in Kolaka Regency. (2) The influence of Consumer Involvement on increasing Brand loyalty for Suzuki Brand Motorcycle Users in Kolaka Regency. This study adopts a quantitative methodology; to collect data, it makes use of observation, literature review, and questionnaire distribution. All riders of Suzuki Brand Motorcycles in Kolaka Regency make up the study's population. whereas 120 persons made up the study's sample. Testing With SPSS 25.0, this research tool does validity and reliability tests. This study employed data analysis methods, specifically, the evaluation of the measurement model (outer model) and the examination of the structural model (inner model) using Smart PLS 4.0. A t-statistic value of 6,545 with a P-Value of 0.000 and a t-statistic value of 2,375 with a P-Value of 0.019, respectively, show that there is a positive and significant relationship between the variable perceived brand value and brand loyalty, and between the variable consumer involvement and brand loyalty.